Application of Online Food Sales Based on Android (A Case Study of UMKM Pink Donuts) - Okyk Fauzi Yudha Permana; Nuril Lutvi Azizah (Universitas Muhammadiyah Sidoarjo, 2022)
MSMEs Pink Donuts is a Micro, Small, and Medium Enterprise business that is engaged in the sale of a variety of donuts that are sold in general to the public. At this time the Pink Donuts sales system still uses an offline system, this makes it difficult for buyers who have to go to the offline outlet and manually record orders from buyers. Based on the analysis of the problems faced by Pink Donuts MSMEs, then one way to be taken is to create an Android-based application to make it easier for buyers and the performance of Pink Donuts MSMEs owners. Applications are made using Open Source IDE Tools, namely Kodular, and PHP as the programming language with MySQL as database management. The final result obtained is an android-based online food sales information system used by Pink Donuts MSMEs. This system is able to provide food menu promotions at Outlets with payment through the Cash On Delivery (COD) system and it is hoped that Pink Donuts will become an MSMEs Go Digital.